2020
DOI: 10.22599/bioj.154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aniseikonia in Anisometropia and Amblyopia

Abstract: Purpose: Clinically, aniseikonia (a perceived difference in shape and image size between the eyes) is often neglected in anisometropic amblyopia due to assumed measurement difficulties. Therefore, we currently lack evidence on whether correction of aniseikonia is beneficial. This study aimed to determine whether subjective aniseikonia is measurable in anisometropia with or without amblyopia. Methods: Participants (15-52 years) with Anisometropic Amblyopia (n = 7), Anisometropia without amblyopia (n = 6) and Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This finding supports the optical approximation and empirical rule of 1% aniseikonia per 1.00D of anisometropia [1,[42][43][44][45]. In contrast, other earlier studies reported that aniseikonia per 1.00 D of anisometropia was less than 1.0%/D [20,46]. These earlier studies evaluated aniseikonia using direct comparison methods, such as New Aniseikonia Tests (HANDAYA Inc., Tokyo, Japan) and Aniseikonia Inspector (Optical Diagnostics, Culemborg, The Netherlands).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding supports the optical approximation and empirical rule of 1% aniseikonia per 1.00D of anisometropia [1,[42][43][44][45]. In contrast, other earlier studies reported that aniseikonia per 1.00 D of anisometropia was less than 1.0%/D [20,46]. These earlier studies evaluated aniseikonia using direct comparison methods, such as New Aniseikonia Tests (HANDAYA Inc., Tokyo, Japan) and Aniseikonia Inspector (Optical Diagnostics, Culemborg, The Netherlands).…”
Section: Discussionsupporting
confidence: 76%
“…The direct comparison method underestimates aniseikonia because of the influence of peripheral fusion and sensory adaptation to cancel out image differences caused by aniseikonia in binocular vision [24][25][26][27]. South et al showed that the amount of aniseikonia in the patients with anisometropic amblyopia had significant variation [20]. Moreover, El-Abedin Rajab et al reported that the direct comparison method in axial anisometropia did not produce indications of significant aniseikonia [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aniseikonia is likely to be present in those with anisometropic amblyopia [ 27 , 28 ]. The difference in images sizes could potentially hinder binocular vision.…”
Section: Methodsmentioning
confidence: 99%
“…Since little is known about the effects of aniseikonia on visual development or the potential benefits of correction (South et al, 2020), we conducted a series of experiments to simulate the effects of aniseikonia. We achieve this by simply scaling up the right image by a certain factor and cutting the edges so left and right images retain the same size.…”
Section: )mentioning
confidence: 99%